Nötkreaturens val av betesvegetation på naturliga betesmarker - Pelve, Maja (SLU/Dept. of Animal Nutrition and Management (until 231231), 2007)
This study concerns the type of vegetation selected by cattle grazing on semi-natural pastures, and whether the selection depends on the nutrient content of the vegetation or on other factors.